An investigation into the principals' leadership roles in selected schools in the Ohangwena Region in Namibia: case study - Shitana, Silas Shituleipo (Rhodes University, Faculty of Education, Department of Education, 2012)
School leadership in Namibia over past centuries was characterized by 'top down' administration and typically proceeded without participation of those involved other than the principals who were the sole decision makers. The notion of school leadership through teamwork (team leadership) in Namibia was formalized after the advent of democracy in 1990 and the subsequent reorganization of the education system. The notion of team leadership is embedded in theories that stress participation, teamwork and distributed leadership. It is against this background that this study sought to investigate the current understandings of school leadership and application of team leadership among principals in selected schools in the Ohangwena region in Namibia. The study is an interpretive case study of two secondary schools in the above" mentioned region in Namibia. The research utilized three quantitative data gathering techniques, namely semi" structured interviews, observation and document analysis. The research participants were two principals, two teachers and two school board members from each research school. The main findings of this study revealed that the notion of participation of all stakeholders in education is seen as a fundamental aspect of the current leadership thinking. However, the respondents' vision of leadership is limited and quite traditional in many ways. There is emphasis on the need to control, monitor, and delegate rather than team leadership. Furthermore, where consultation is mentioned it seems the respondents think of the passing down of information "“ a cascade model " as consultation, a view that is narrow and inaccurate in terms of contemporary leadership theories. While there was an appreciation of the benefits derived from team leadership, challenges facing such leadership pervaded responses. These included lack of understanding of government policies such as ETSIP and NSPIs, resistance to change and implementation of policy. The study recommends that leadership and management programs and teacher leadership development programs be established in Namibia. Finally, the study recommends further research to include Learner Representative Council and Heads of Department. These stakeholders in education may provide new insights into the current school leadership thinking.
Keywords: School management and organization -- Namibia -- Ohangwena; School principals -- Namibia -- Ohangwena; Educational leadership -- Namibia -- Ohangwena; Educational change -- Namibia -- Ohangwena; Management -- Employee participation -- Namibia -- Ohangwena